EFEKTIVITAS MATERI AJAR GERAK LURUS BERMUATAN AUTHENTIC LEARNING UNTUK MELATIHKAN KETERAMPILAN PEMECAHAN MASALAH - Supriyadi, Supriyadi; Wati, Mustika; Miriam, Sarah; Sasmita, Fauzia Dwi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
The lack of modules that could train problem-solving skills gave impacts students’ problem-solving skills, which are in the low category. This research focused on describing the effectiveness of the physics modules which enrich authentic learning on straight-line motion subjects. This research and development within the ASSURE model use a one-group pretest-posttest design and thus tested on 85 students of X IPA Senior High School 6 Banjarmasin. The data collection technique was obtained by test instruments for pre-test and post-test, thus analyzed by the N-Gain test and t-test. The results showed that the effectiveness of the authentic learning module, which enriches authentic learning, was categorized as high, and the two-way significance of the test was 0.00 (< 0.05), which indicated that there was a difference in the average students’ learning outcomes before and after using the authentic learning module. Thus, it can be concluded that the module containing authentic learning in straight-motion material is effectively used in physics learning to train students’ problem-solving skills.